Zwitterionic Moieties from the Huisgen Reaction-A Case Study with Amphiphilic Dendritic Assemblies - Ramireddy, Rajasekhar R. (2013)
Supramolecular nano-assemblies that reduce non-specific interactions with biological macromolecules, such as proteins, are of great importance for various biological applications. Recently, zwitterionic materials have been shown to reduce non-specific interactions with biomolecules, owing both to their charge neutrality and their ability to form strong hydration layer around zwitterions via electrostatic interactions. In this article, we present new triazole-based zwitterionic moieties that are incorporated as the hydrophilic functionalities in facially amphiphilic dendrons. The amphiphilic zwitterionic dendrons spontaneously self-assemble in aqueous solutions forming micelle-type aggregates, which are confirmed by DLS, TEM, and fluorescence techniques. We also compare the structural and functional characteristics of the zwitterionic dendrons with the corresponding charge-neutral PEG-based dendrons and anionic carboxylate-based dendrons. Surface charge measurements, temperature sensitivity and evaluation of interactions of these assemblies with proteins form the bases for these comparisons.